Obesitas pada Anak : Penyebab dan Konsekuensi Jangka Panjang - Ananda Fitriliani; Bayu Anggileo Pramesona; Shinta Nareswari (CV. Jasa Sukses Abadi, 2023)
Obesity in children has reached epidemic levels in both developed and developing countries. Overweight and obesity in childhood are known to have a significant impact on physical and psychological health. Overweight and obese children tend to be obese into adulthood and are more likely to develop non-communicable diseases such as diabetes and cardiovascular disease at a younger age. The mechanism of obesity is not fully understood and is believed to be a disorder with various causes. In general, overweight and obesity are assumed to result from increased calorie and fat intake. On the other hand, there is supporting evidence that excessive sugar intake through soft drinks, an increase in portion size, and a steady decline in physical activity play a major role in the increase in obesity rates worldwide. Child obesity can greatly affect children's physical, social and emotional well-being, and self-confidence. It is also associated with poor academic performance and a lower quality of life experienced by children. Many comorbid conditions such as metabolic, cardiovascular, orthopedic, neurological, hepatic, pulmonary, and renal disorders have also been seen to be associated with childhood obesity. The growing problem of childhood obesity can be slowed, if society focuses on its causes. Overweight and obesity cannot be solved through individual actions alone. A comprehensive response is needed to create a healthy environment that can support individuals in making healthy choices based on knowledge and skills related to health and nutrition. This response requires government commitment and leadership, long-term investment, and whole-of-society engagement to protect children's right to good health and well-being. Progress can be made if all actors remain committed to working together towards the common goal of ending childhood obesity. This literature review discusses obesity in children by explaining what risk factors influence and long-term consequences for children.